2021
DOI: 10.1002/pmrj.12592
|View full text |Cite
|
Sign up to set email alerts
|

Forearm flexor injury is associated with medial ulnar collateral ligament injury in throwing athletes

Abstract: Background Elbow ulnar collateral ligament (UCL) injuries have become increasingly common in throwing athletes. The forearm flexors (FF) have been studied as biomechanical stabilizers for the medial elbow. However, there are no studies investigating the association of concomitant UCL injuries and FF injuries in throwing athletes. Objective To determine if throwing athletes with a complete UCL injury had a greater likelihood of concomitant FF injury than those with a partial UCL injury. Design Descriptive retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…The results of this study showed that three or more parameters were performed correctly in 80.7% and 64% of pitchers in the age groups of 14 to 18 years and 9 to 13 years, respectively. This study also shows that a better technique generates lower humeral internal rotation torque and a lower elbow valgus load, preventing shoulder and elbow pain in adolescent athletes (35).…”
Section: Preventionsupporting
confidence: 58%
See 1 more Smart Citation
“…The results of this study showed that three or more parameters were performed correctly in 80.7% and 64% of pitchers in the age groups of 14 to 18 years and 9 to 13 years, respectively. This study also shows that a better technique generates lower humeral internal rotation torque and a lower elbow valgus load, preventing shoulder and elbow pain in adolescent athletes (35).…”
Section: Preventionsupporting
confidence: 58%
“…Before physical examination, history taking is necessary to determine the kind of injury, history of previous injuries, and/or overtraining practices (Table 2) (34). It is imperative to know if the pain was sudden or developed overtime and which throwing motion phase causes the pain, as different anatomical structures are involved in each phase (35). Athletes also may report discomfort while throwing and decreased performance.…”
Section: History Presentation and Physical Examination Findingsmentioning
confidence: 99%
“…Similarly, an epidemiological study examining injuries to track and field athletes found that athletes competing in throwing and shot put events reported elbow ligament injuries more often than any other injury (14). When assessing UCL injuries, the forearm flexor musculature also must be evaluated as previous research has found a strong association between UCL injury and forearm flexor injury (15). The limited literature has shown that UCL injuries are prevalent in javelin throwers, and additional research on UCL injuries in this population is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased fatigue in the forearm flexor muscles may increase the burden imposed on the UCL, which can ultimately increase the likelihood of UCL injury. In fact, some studies have revealed the close relationship between forearm flexor injury and UCL tear in throwing athletes including baseball pitchers 51–53 . Ikezu et al 52 reported that combined UCL and flexor‐pronator muscle injuries were observed in 45 of 99 baseball players (91 pitchers and 8 fielders), of which 40 of 45 (89%) involved injury of the flexor digitorum superficialis.…”
Section: Discussionmentioning
confidence: 99%